PERLINDUNGAN HUKUM PEKERJA DALAM PROSES HUBUNGAN INDUSTRIAL - Kunarto S.H., M.H. (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2012)
Legal protection of workers in the industrial relations process is essential in order to improve and grow the national economy, but the relationship of workers, employers and government (tripartite) in the industrialized world is increasingly apparent lack of harmony and need to get attention by all parties. These products of labor law which are made by the government biased towards employer and seem only to increase taxes and foreign exchange. The implications of globalization have changed the industrialization, trade and the world economy into a form of business. For Indonesia, the era of globalization means that it faced a huge challenge, which means there must be readiness for business and human resource potential, so they can compete in international markets, in terms of the law needs to be improved, so as to provide protection for workers.